Modal Manusia dan Perbezaan Pendapatan Ketua Isi Rumah Bekerja Mengikut Wilayah di Malaysia (Sains Humanika, 2011)
The Malaysian government has given main emphasis on human resoucedevelopment to enhance human capital possession amongst its population and at the same time to increase their income. Although Malaysia has shown a tremendous success in reducing the poverty level, the issue of income inequality especially among regions and ethnicity remainsunresolved. This article aims to analyze the effect of human capital on income distribution among the working head of households in the Central and East Regions of Peninsular Malaysia. Analysis in this article is based on the data collected through a field survey conducted in 2007/08. Theanalysis consists of two levels. The first level estimates the effect of human capital variables on the head of household’s income level using income model developed by Mincer (1974). The second level decomposes determinants of income differentials using decomposition model developed by Blinder (1973). The study finds that human capital variables significantly determine the level of income as well as income differentials among the head of households by regions. Further, the result shows that 74.9 percent of the head of household’s income differentials are unexplained and this portion is related to employers’ discriminatory practice.
Keywords: Human capital; income differentials; Central Region; East Region